The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0166799
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Either a Mirror, Internal or External Focus Instructions on Single and Multi-Joint Tasks

Abstract: Training in front of mirrors is common, yet little is known about how the use of mirrors effects muscle force production. Accordingly, we investigated how performing in front of a mirror influences performance in single and multi-joint tasks, and compared the mirror condition to the established performance effects of internal focus (IF) and external focus (EF) instructions in a two part experiment. In the single-joint experiment 28 resistance-trained participants (14 males and 14 females) completed two elbow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Therefore, 28 full-text papers were read. Nineteen studies were excluded after reading the full texts, and a total of nine studies were included in the review [13][14][15][16][25][26][27][28][29]. There were 555 search results in the secondary searches, and one additional study was included in the review [30].…”
Section: Search Resultsmentioning
confidence: 99%
“…Therefore, 28 full-text papers were read. Nineteen studies were excluded after reading the full texts, and a total of nine studies were included in the review [13][14][15][16][25][26][27][28][29]. There were 555 search results in the secondary searches, and one additional study was included in the review [30].…”
Section: Search Resultsmentioning
confidence: 99%
“…We describe several studies of brain-related neurophysiological activity associated with different attentional foci, but this area of the literature is nascent and not yet amenable to meta-analytic evaluation. A body of work, nevertheless, has assessed muscular (EMG) activity under EF and IF conditions for tasks involving maximal or submaximal force production (e.g., Greig & Marchant, 2014; Halperin, Hughes et al, 2016; Lohse & Sherwood, 2012; Vance et al, 2004), basketball free-throw shooting (Zachry et al, 2005), or dart throwing (Lohse et al, 2010). We examined EMG activity only in the context of significant behavioral effects of attentional focus.…”
Section: Secondary Analysesmentioning
confidence: 99%
“…Mirror was not utilized for the first nonmirror feedback trial. As for the second mirror feedback trial, procedure was conducted as reported by previous study (Halperin et al, 2016). A full-body sized mirror was placed 1 m away from the subject for a full-body observation by the subjects.…”
Section: Exercise Performancementioning
confidence: 99%
“…Utilizing a mirror for providing information for proper movement during various physical activities has long been recommended. Despite of its popularity in various fitness settings, there have been mixed reports on the advantageous nature of the mirror on the motor performance (Halperin et al, 2016). For example, a study which observed balance exercise in the old people did not show considerable improvement in balance (Vaillant et al, 2004).…”
Section: Introductionmentioning
confidence: 99%